'Like building a plane and flying it all in one go': an interview study of infection prevention and control in Australian general practice during the first 2 years of the SARS-CoV-2 pandemic. Issue 9 (19th September 2022) - Hor, Su-Yin; Burns, Penelope; Yong, Faith R; Barratt, Ruth; Degeling, Chris; Williams Veazey, Leah; Wyer, Mary; Gilbert, Gwendolyn L
Abstract : Objectives: General practitioners (GPs) and their staff have been at the frontline of the SARS-CoV-2 pandemic in Australia. However, their experiences of responding to and managing the risks of viral transmission within their facilities are poorly described. The aim of this study was to describe the experiences, and infection prevention and control (IPC) strategies adopted by general practices, including enablers of and challenges to implementation, to contribute to our understanding of the pandemic response in this critical sector. Design: Semistructured interviews were conducted in person, by telephone or online video conferencing software, between November 2020 and August 2021. Participants: Twenty general practice personnel working in New South Wales, Australia, including nine GPs, one general practice registrar, four registered nurses, one nurse practitioner, two practice managers and two receptionists. Results: Participants described implementing wide-ranging repertoires of IPC strategies—including telehealth, screening of patients and staff, altered clinic layouts and portable outdoor shelters, in addition to appropriate use of personal protective equipment (PPE)—to manage the demands of the SARS-CoV-2 pandemic. Strategies were proactive, influenced by the varied contexts of different practices and the needs and preferences of individual GPs as well as responsive to local, state and national requirements, which changed frequently as the pandemic evolved. Conclusions: Using the 'hierarchy of controls' as a framework for analysis, we found that the different strategies adopted in general practice often functioned in concert with one another. Most strategies, particularly administrative and PPE controls, were subjected to human variability and so were less reliable from a human factors perspective. However, our findings highlight the creativity, resilience and resourcefulness of general practice staff in developing, implementing and adapting their IPC strategies amidst constantly changing pandemic conditions.